A pharmacovigilance study on probiotic preparations based on the FDA Adverse Event Reporting System from 2005 to 2023 - Wang, Yitong; Tan, Weifu; Li, Xuyang; Yang, Guangli; Wang, Yunxiao; Liao, Jing; Lu, Aner; Zhang, Guoqing; Chen, Kuidai; Yang, Liling; Li, Wei (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundProbiotics are recognized as beneficial foods, but adverse reactions reported by individuals still exist. This study aims to analysis adverse events (AE) related to probiotics from the FAERS database from the first quarter (Q1) of 2005 to the fourth quarter (Q4) of 2023.MethodsThe AE data related to probiotic from the 2005 Q1 to the 2023 Q4 were collected. R language was applied to analyze the standardized AE data and three algorithms including the reporting odds ratio (ROR), the proportional reporting ratio (PRR) and the empirical Bayes geometric mean (EBGM) were used to identify AE signals.ResultsIn this study, 10,698,312 reports were collected from the FAERS database, of which 74 probiotic-related adverse events were reported. About one third of the reported cases were older than 60 years.36.36% of the reported cases required Hospitalization. A total of 285 preference terms (PTS) and 15 system organ classes (SOC) were identified. In the overall analysis, only 9 PTs and 2 SOCs met significant disproportionality for all three algorithms simultaneously. SOCs included Gastrointestinal disorders (N=97, ROR=5.3, PRR=3.84, EBGM=3.84) and Hepatobiliary disorders (N=9, ROR =3.39, PRR=3.32, EBGM=3.32). PTs included Gastrointestinal pain (ROR=77.76, PRR=76.69, EBGM=76.63), Hypophagia (ROR=24.13, PRR=23.88, EBGM=28.88), and Hepatobiliary disorders (N=97, ROR=5.3, PRR=3.84, EBGM=3.84) and Flatulence (ROR=23.75, PRR=23.28, EBGM=23.27) were the top four highest. Meanwhile, s found new unique adverse signals such as Agitation (ROR=12.48, PRR=12.32, EBGM=12.32) and Anxiety (ROR=4.10, PRR=4.04, EBGM=4.04). Additionally, subgroup analyses were performed to identify AE signals based on gender and age. Metabolism and nutrition disorders (N=6, ROR=3.21, PRR=3.04, EBGM=3.04) and Asthenia (N=3, ROR=5.9, PRR=5.71, EBGM=5.71) were unique AE signal for the male group.ConclusionAlthough, the risk of adverse reactions arising from the application of probiotics cannot be ignored. However, However, the results of this FAERS-based study continue to support the overall safety of probiotic preparations. It is necessary to pay attention to the potential influence of factors such as gender and age on the effects and adverse reactions of probiotic application in basic research and clinical application.